Corrections to “Resonances in Bianisotropic Layers” - Faroq Razzaz; Majeed A. S. Alkanhal (IEEE Photonics Journal)
Presents corrections to the paper, “Resonances in bianisotropic layers,” (Razzaz, F. and Alkanhal, M.A.S.), IEEE Photon. J., vol. 10, no. 1, 2018, Art. no. 6100112.